Exploring the dual role of B cells in solid tumors: implications for head and neck squamous cell carcinoma - Bao, Jiantong; Betzler, Annika C.; Heß, Jochen; Brunner, Cornelia (Frontiers in immunology, 2023)
In the tumor milieu of head and neck squamous cell carcinoma (HNSCC), distinct B cell subpopulations are present, which exert either pro- or anti-tumor activities. Multiple factors, including hypoxia, cytokines, interactions with tumor cells, and other immune infiltrating lymphocytes (TILs), alter the equilibrium between the dual roles of B cells leading to cancerogenesis. Certain B cell subsets in the tumor microenvironment (TME) exhibit immunosuppressive function. These cells are known as regulatory B (Breg) cells. Breg cells suppress immune responses by secreting a series of immunosuppressive cytokines, including IL-10, IL-35, TGF-β, granzyme B, and adenosine or dampen effector TILs by intercellular contacts. Multiple Breg phenotypes have been discovered in human and mouse cancer models. However, when compartmentalized within a tertiary lymphoid structure (TLS), B cells predominantly play anti-tumor effects. A mature TLS contains a CD20+ B cell zone with several important types of B cells, including germinal-center like B cells, antibody-secreting plasma cells, and memory B cells. They kill tumor cells via antibody-dependent cytotoxicity and phagocytosis, and local complement activation effects. TLSs are also privileged sites for local T and B cell coordination and activation. Nonetheless, in some cases, TLSs may serve as a niche for hidden tumor cells and indicate a bad prognosis. Thus, TIL-B cells exhibit bidirectional immune-modulatory activity and are responsive to a variety of immunotherapies. In this review, we discuss the functional distinctions between immunosuppressive Breg cells and immunogenic effector B cells that mature within TLSs with the focus on tumors of HNSCC patients. Additionally, we review contemporary immunotherapies that aim to target TIL-B cells. For the development of innovative therapeutic approaches to complement T-cell-based immunotherapy, a full understanding of either effector B cells or Breg cells is necessary.